INDONESIAN WOMEN’S PARTICIPATION IN POLITICS AND GOVERNANCE: CHALLENGES AND OPPORTUNITIES (Proceedings of the International Conference on Future of Women, 2018)
The number of influential women leaders in Indonesia’s public arena has increased significantly in the last ten years.  Indonesian women assume leadership in political parties, legislative assembly, national government departments and the judiciary.  This paper discusses challenges and best practices which enable Indonesian women to actively and successfully participate in the public sphere both in the political and government arena.  This paper is based on the research entitled “Indonesian Women’s Participation in Politics” funded by Universitas Bakrie, Jakarta in 2015-2016.  Barriers for women’s participation in politics and government include lack of resources to finance a campaign or to finance necessities of a successful mandate, public private divide of social space (women as mothers, wives, daughters, daughter in laws), political violence, ideological polarization and patriarchal gender ideology, gender role prescriptions and honor conceptions, sexist and hostile political climate in parliaments and government departments and the lack of psychological empowerment among Indonesian women. Best practices which enable and facilitate women’s participation in politics and government in Indonesia include gender mainstreaming through laws and legislations, quotas for women in political parties, parliaments, civil service, judiciaries, executive government departments, sustained and legally supported budgeting for ensuring women’s empowerment and participation, grass root social and political empowerment at the local regency level for political recruitment through mentors, regional political party branches and local religious and secular organizations, political education to young girls at schools and universities from the national level to the regional and local levels, diplomacy, negotiating and brokering a form of participative democracy in the context of present political ideologies from sub-national to national level politics and governance
Keywords: patriarchal gender ideology; ideological polarization; participative democracy; gender mainstreaming; quotas; political recruitment; diplomacy; brokering